THE DEVELOPMENT OF INDONESIAN MARITIME POTENTIAL AND PROSPECTS TOWARDS A WORLD MARITIME AXIS - Anton Nugroho; Okol Sri Suharyo; Abdul Rahman (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Indonesia is the largest archipelagic country in the world with a strategic position between two continents, namely the Asian Continent and the Australian Continent and also between two oceans, namely the Indian Ocean and the Pacific Ocean with more than 17,000 islands and an area that is generally approximately 70% complete. from the ocean. With its enormous potential, the success of creating a maritime sector with high economic value will have a positive impact on economic equality. It takes a lot of effort to be able to realize a reliable marine sector that has a major contribution to the national economy. Indonesia's position in the middle of the world of cross-band trade has made Indonesia have the ambition to become a maritime axis country. And one way is by preserving the enormous potential and natural marine resources that we have, all of which are only to prepare Indonesia to become a world maritime axis. Keywords: Strategic Position, Economic Equality, The World's Maritime Axis